Using a Self-Determination Theory Approach to Understand Student Perceptions of Inquiry-Based Learning (Teaching and Learning Inquiry, 2021)
Inquiry-based laboratory activities, as a part of science curricula, have been advocated to increase students’ learning outcomes and improve students’ learning experiences, but students sometimes struggle with open-inquiry activities. This study aims to investigate students’ perceptions of inquiry-based learning in a set of laboratory activities, specifically from a psychological (i.e., Self-Determination Theory) perspective. Students’ ratings of the level of inquiry in these activities indicate that students’ perceptions of inquiry align with the instructor-intended amount of inquiry in each exercise. Students’ written responses, explaining their ratings, indicate that students’ perceptions of the amount of inquiry in a given lab exercise relate to their feeling of freedom (or autonomy), competence, and relatedness (or support), during the inquiry-based learning activities. The results imply that instructors implementing inquiry-based learning activities should consider student motivation, and Self-Determination Theory can be a useful diagnostic tool during teaching development.